Combined Annoyance Assessment of Subway Train-Induced Structural Vibration and Ambient Noise - Ke Sun; Wei Zhang (Shock and Vibration, 2016)
The subway train-induced structural vibration and ambient noise may cause annoyance and other negative influences on the human body. Presently, limited models have been developed to execute the quantitative evaluation of the combined annoyance caused by both structural vibration and ambient noise. In this study, a fuzzy membership function and normal distribution function were coupled to describe the fuzziness and randomness of human annoyance responses; a novel annoyance evaluation model was proposed to assess the structural vibration and ambient noise; and the annoyance of human was classified into six grades. Subsequently, we integrated an actual case into this study to calculate and analyze the combined annoyance degree. The applied results were compared with the standard limits, in which the rationality and superiority of the proposed model were verified. The results exhibit the notion that the proposed models perform well and can serve as a reference for spatial planning and development in the nearby subway environment.